Improving Teacher Competence through SDGS-Based Learning Design Training: A Practice-Based Approach Using Black Soldier Fly Cultivation - Ulfi Faizah; Muji Sri Prastiwi; Nur Ainiyah; Walib Abdullah; Dian Permatasari Kusuma Dayu; Dwi Setyo Pratiwi (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: Teachers at Insan Cendekia Mandiri Boarding School, Sidoarjo, needed the initiative to bridge the gap between theory and practice. We knew that educators need more than just concepts, so we provide hands-on training to help them design SDG-based lessons that effectively instill sustainability values directly in the classroom.Objectives:　This community service program aimed to improving teacher competence through SDGs-based learning design training: a practice-based approach using                 black soldier fly cultivation. Teachers at Insan Cendekia Mandiri Boarding School, Sidoarjo empowered through a workshop on SDG-based lesson design with essential sustainability values.Methods: This community service activity was conducted through a workshop-based approach. The program began with an introduction to SDG-based learning models and methods, followed by the development of relevant teaching materials and media. It also included hands-on workshops and learning simulations using black soldier fly cultivation, concluding with continuous evaluation and long-term mentorship.Result: The program successfully empowered the teachers through three core achievements: a deeper understanding of SDG-based design and black soldier fly cultivation proven by improved test scores; a wealth of innovative strategies for the curriculum; and the practical skills to bring these lessons to life. The teachers' enthusiastic response reflected a newfound confidence in leading sustainable learning.Conclusion: This community service program has successfully improving teacher competence through SDGs-based learning design training with a practice-based approach using black soldier fly cultivation empowered teachers at Insan Cendekia Mandiri Boarding School, Sidoarjo. Through specialized training in SDG-based lesson design, we have equipped educators with the tools and knowledge needed to share essential sustainability values with their students.